2014
DOI: 10.1167/iovs.14-14153
|View full text |Cite
|
Sign up to set email alerts
|

Focal Relationship Between Structure and Function Within the Central 10 Degrees in Glaucoma

Abstract: The GCC is the most useful parameter to evaluate structure and function within the central 10° in glaucoma. Adjusting for RGC displacement is essential to evaluate the relationship between structure of the GCL-related layer and function at the central macula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
57
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 24 publications
10
57
0
2
Order By: Relevance
“…Our findings are in agreement with the previous studies which reported that adjusting the location of central VF test locations for RGC displacement improved the correlations for the four paracentral points although this improvement did not reach statistical significance 8 9. The reason for this location-dependent effect may be that the displacement of the macular GCs from the corresponding cones is maximal closest to the fovea 3 8 9. A previous study similarly reported that inferotemporal GC/IPL thickness had the highest correlation with corresponding sensitivities on microperimetry superotemporally 23.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are in agreement with the previous studies which reported that adjusting the location of central VF test locations for RGC displacement improved the correlations for the four paracentral points although this improvement did not reach statistical significance 8 9. The reason for this location-dependent effect may be that the displacement of the macular GCs from the corresponding cones is maximal closest to the fovea 3 8 9. A previous study similarly reported that inferotemporal GC/IPL thickness had the highest correlation with corresponding sensitivities on microperimetry superotemporally 23.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with those of earlier studies, which found a severity-dependent association between macular structure and function in patients with glaucoma 9 24. Ohkubo et al 9 reported that GC/IPL thickness of most of the upper half of the macula did not significantly correlate with VF sensitivities in eyes with early glaucoma.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For instance some authors reported that after considering this ''on average'' ganglion cell displacement in the macula, the sectorial structure-function relationship in glaucoma improves, 3,9 especially within the central 108 of the visual field. More recently, Turpin et al 10 have published a method for customizing such mapping based on an individual person's retinal ganglion cell plus inner plexiform layers (RGCþIPL) profiles obtained from macular OCT scans.…”
mentioning
confidence: 99%